Effects of carbon monoxide addition on the sooting characteristics of ethylene and propane counterflow diffusion flames. (1st July 2020) - Dai, Wei; Yan, Fuwu; Xu, Lei; Zhou, Mengxiang; Wang, Yu
Abstract: In this work, the effects of the addition of carbon monoxide (CO) on soot formation were investigated for ethylene and propane counterflow diffusion flames (CDFs). The work was partly motivated by experimental observations that the addition of CO monotonically reduced the sooting tendencies of ethylene diffusion flames; while it had an interesting non-monotonic influence on soot formation in propane flames. Quantitative laser-based soot measurements were performed in combination with numerical simulations using detailed soot models to provide kinetic insights into the role of CO in the soot evolution processes. To isolate the chemical effect of CO from dilution effects, additional studies on the effects of N2 addition were performed and the results were compared with those with CO addition. For ethylene flames, the experimental data and numerical results agreed to show that the addition of CO monotonically reduced soot formation, primarily due to its dilution effect. For propane flames, interestingly, the peak soot volume fraction was found to be slightly increased with 10% CO addition; higher level of CO addition finally led to a reduction of soot formation, but the quantitative extent of the reduction was much smaller as compared to that in the ethylene flame. In flames of both fuels, CO addition was seen to lead to a higher soot volume fraction than the same amount of N2 addition, indicating that CO chemically promoted soot formation. Further analysis showed that the chemical promoting effects of CO in propane flames was stronger than that of ethylene flames, which was due primarily to the different role CO played in the precursor formation /soot inception processes.